Hydrodynamic vibration analysis of preloaded/loaded forklift using a hydraulic cylinder - Ong Kiat Teng (2023)
"Hydrodynamic Vibration Analysis Of Preloaded/Loaded Forklift using a Hydraulic Cylinder" is the title of the author's Final Year Project under Vibration area.